The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1016/s0038-1098(00)00073-9
|View full text |Cite
|
Sign up to set email alerts
|

Broad histogram method for multiparametric Hamiltonians

Abstract: We extended the Broad Histogram Method in order to obtain spectral degeneracies for systems with multiparametric Hamiltonians. As examples we obtained the critical lines for the square lattice Ising model with nearest and next-nearest neighbor interactions and the antiferromagnetic Ising model in an external field. For each system, the entire critical line is obtained using data from a single computer run. We also discuss the accuracy and efficiency of our method.PACS numbers: 02.70.Lq, 05.50.+q, 75.10.HkThe s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…We will now be recording, again in the high-levels of the WL diffusion process, the cumu-lative (exchange-energy, field-energy) two-parametric histograms, in order to produce an approximation for the two-parametric DOS of the RFIM. At this point, we should stress that any multi-parametric WL process is inevitably restricted to rather small lattices [62,74,75,76,77]. In fact the applications of such multi-parametric methods are substantially limited, since besides the immense time and excessive memory requirements, they very often face severe ergodic and/or convergence problems, depending on both the physical system and the algorithmic implementation.…”
Section: Numerical Approachmentioning
confidence: 99%
“…We will now be recording, again in the high-levels of the WL diffusion process, the cumu-lative (exchange-energy, field-energy) two-parametric histograms, in order to produce an approximation for the two-parametric DOS of the RFIM. At this point, we should stress that any multi-parametric WL process is inevitably restricted to rather small lattices [62,74,75,76,77]. In fact the applications of such multi-parametric methods are substantially limited, since besides the immense time and excessive memory requirements, they very often face severe ergodic and/or convergence problems, depending on both the physical system and the algorithmic implementation.…”
Section: Numerical Approachmentioning
confidence: 99%
“…The title compound of [N(CH 3 ) 4 ][N(C 2 H 5 ) 4 ]ZnCl 4 was synthesized starting from precursor N(CH 3 ) 4 Cl, N (C 2 H 5 ) 4 Cl, and ZnCl 2 of high purity (more than 99.9%). The precursors were weighted in the stoichiometric proportion in conformity with the following equation, then dissolved in a minimum quantity of water and finally mixed.…”
Section: Methodsmentioning
confidence: 99%
“…The crystal structure of the [N(CH 3 ) 4 ][N(C 2 H 5 ) 4 ]ZnCl 4 compound can be described by alternating organic layers (TEA) 2+ and organic-inorganic layers [(TMA) + /ZnCl 4 2− ] parallel to the (0 1 0) plane (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1. From both numerical [2,11] and analytical [10,12] approaches, it was shown that in the plane of the reduced temperature kT /J 1 against the competition parameter −J 2 /J 1 , the phase diagram presents ferromagnetic, paramagnetic and super-antiferromagnetic phases. The critical line between the ferromagnetic and paramagnetic phases belongs to the universality class of the two-dimensional Ising model, whereas the critical exponents along the critical line separating the SAF ordered phase from the the paramagnetic phase are found to be non-universal.…”
Section: Introductionmentioning
confidence: 99%